Pengaruh Aktivitas Seni Terhadap Kesehatan Mental Mahasiswa di Lingkungan Kampus - Syafi’i Syafi’i (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
Arts activities have long been recognized as an effective means of self-expression, particularly in reducing stress and improving mental well-being. This study aims to explore the influence of arts activities on students' mental health in a campus environment. Through a mixed methodology approach that included quantitative surveys, qualitative interviews, and participant observation, this study involved students from various majors who were involved in arts programs such as painting, music, and theater. The results showed that participation in arts activities had a significant positive impact, namely a reduction in stress levels, an increase in emotional well-being, and the creation of a deep sense of community among students. This study suggests that the integration of arts programs in the campus curriculum can be one solution to support the mental health of students who are increasingly stressed by various academic and social factors.